0809 A Randomized Double-blind, Placebo Controlled Trial With Cross-over, To Assess The Efficacy Of Correcting Vitamin D Deficiency In Improving The Symptoms Of Restless Legs Syndrome (RLS). (27th May 2020) - Wong, J; Gupta, D; Nadhim, A; Bhat, S; Polos, P
Abstract: Introduction: Recent studies have shown an association of low Vitamin D levels and severity of RLS symptoms. However, effect of treatment of Vit D deficiency on RLS symptoms was not reported, nor were other exacerbating factors for RLS such as iron deficiency or OSA addressed in prior studies, but have been addressed in our study. Methods: This is an ongoing study at the JFKMC Sleep Clinic. Eligible Patients with RLS include those with vitamin D 25, hydroxy deficiency (<20 ng/ml), or insufficiency (<30 ng/ml). Such patients will be enrolled in the study after comorbid conditions like iron deficiency and OSA have been adequately corrected. Randomization of the patients will be done by the JFK pharmacy so the patient and provider are blinded to the substance. Substance A or B could be either Vitamin D3 Capsule 50, 000 IU, or placebo. Each patient takes A for 6 weeks and then crosses over to B for 6 weeks. Weekly iRLS questionnaires will be collected. Actiwatch Device, to assess activity count per minute, will be worn on the ankle at night for one week time periods: at baseline, at end of 6 weeks of taking A and then at the end of 6 weeks of taking B. Vitamin D levels will also be assessed after each course of supplementation and correlated with subjective and objective findings. Results: Between July 7, 2019 to current, 50 consecutive patients seen in sleep clinic with RLS were assessed for vitamin D levels. Ages ranged from 23-86 years. 27 patients were female (54%). Two patients met inclusion criteria and have started their 13-week study. Conclusion: This study will help to establish the role of Vitamin D deficiency as a risk factor for RLS, independent of ferritin levels, and comorbid OSA, in affected individuals. This may help to discover a potentially treatable form of RLS. Support: No financial support.